Disruption of neuronal nitric oxide synthase dimerization contributes to the development of Alzheimer's disease: Involvement of cyclin-dependent kinase 5-mediated phosphorylation of neuronal nitric oxide synthase at Ser293. (October 2016) - Kwon, Kyoung Ja; Park, Jung-Hyun; Jo, Inho; Song, Kee-Ho; Han, Jung-Soo; Park, Seung Hwa; Han, Seol-Heui; Cho, Du-Hyong
Abstract: Although previous studies have suggested that neuronal nitric oxide synthase (nNOS)-derived NO has neuroprotective effects on the development of Alzheimer's disease (AD), the underlying molecular mechanisms are not fully elucidated. Here, we investigated whether and how disruption of nNOS dimerization contributes to the development of AD. No differences in synaptic number or expression of synaptic markers, including synaptophysin and postsynaptic density 95, were found in the cortex of 5 × FAD mice, which possess 5 familial AD mutations, at 6 months of age compared with control littermates. nNOS dimerization was disrupted in the 5 × FAD cortex, accompanied by an increase in reactive oxygen species (ROS) production. The subcellular distribution of cyclin-dependent kinase 5 (CDK5) shifted more diffusely toward a cytosolic compartment, but there was no change in total expression. Furthermore, the levels of p25, a CDK5 activator, increased significantly and it colocalized with nNOS in the 5 × FAD cortex. In silico analysis revealed that a new nNOS-specific GSP (glycine-serine-proline) motif was well-conserved across species at nNOS-Ser 293, which is located ahead of the N-terminal hook. This motif was not present in the closely related isoform, endothelial NOS. Motif scan analysis also predicted that CDK5 can phosphorylate nNOS-Ser 293 with a high likelihood. An in vitro phosphorylation assay clearly showed that CDK5/p25 does indeed phosphorylate nNOS-Ser 293 . Finally, nNOS-S293D mutant, a phosphomimetic form of nNOS-Ser 293, and nNOS-S293A mutant, a neutral form of nNOS-Ser 293, significantly decreased nNOS dimerization and NO production. Taken together, our results demonstrate that nNOS dimers are disrupted in the 5 × FAD cortex, and nNOS-Ser 293, a potential site of CDK5 phosphorylation, may be involved in the decrease in nNOS dimerization and NO production, and the development of AD. Graphical abstract: Highlights: nNOS dimerization is disrupted and ROS production is elevated in the frontal cortex of 5 × FAD mice at 6 months of age. Expression of p25 protein is elevated. nNOS protein is colocalized with the increased level of p25 protein. CDK5 phosphorylates nNOS-Ser 293 in vitro, and mutations of nNOS-Ser 293 disrupt nNOS dimerization and decrease NO production.